Багатоточкова задача для параболічного рівняння зі змінними коефіцієнтами - Пташник, Б.Й.; Тимків, І.Р. (Видавничий дім "Академперіодика" НАН України, 2008)
The correctness of a problem with multipoint conditions with respect to the time for the Petrovskii parabolic equation with coefficients depending on the spatial coordinate is investigated. The conditions of existence and uniqueness of the solution of the problem are established. The metrical theorems on the lower bounds of small denominators of the problem are proved.